Herpetofauna Diversity at the Central Campus of Padang Air Tawar Barat State University, Padang City, West Sumatra - Alif Nanda Ferdian; fitra nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Herpetofauna comes from the word herpeton, which means reptiles. In the past, before the science of taxonomy developed, amphibians and reptiles were included as one group of animals because they were considered to be both reptiles. With the development of science, they are now two separate groups. Padang State University (UNP) as one of the leading universities in Padang City, West Sumatra, continues to strive to be the best university at the national and international level, by repairing and adding physical buildings and complementing existing infrastructure. One of them is the construction of new buildings in several faculties at UNP. This study aims to find out what herpetofauna exist in UNP and how diverse they are. This study used the Visual Encounter Survey (VES) method. The number of herpetofauna found in UNP was 270 individuals belonging to 7 families, namely Ranidae, Dicroglossidae, Bufonidae, Gekkonidae, Acrochordidae, Scincidae, and Varanidae. The species found were Duttaphrynus melanostictus, Hemidactylus frenatus, Odorrana hosii, Fejervarya cancrivora, Acrochordus granulatus, Eutropis multifasciata, and Varanus salvator. The dominance value in the Padang State University campus area shows the number 0.6415, the richness value is 1.6076 and the species diversity value is 0.7712.